A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand - Sumontha, Montri; Chomngam, Nirut; Phanamphon, Eakarit; Pawangkhanant, Parinya; Viriyapanon, Chutinton; Thanaprayotsak, Wanlada; Pauwels, Olivier S. G. (Zootaxa, 2017)
We describe Dixonius kaweesaki sp. nov. from Khao Daeng, a limestone mountain in Khao Sam Roi Yot massif, Prachuap Khiri Khan Province, peninsular Thailand. It is diagnosed from all other species by a combination of maximal SVL of 41.6 mm; 12 or 13 longitudinal rows of dorsal tubercles; 24 longitudinal rows of ventrals across the abdomen; a continuous series of 9–11 precloacal pores in males, no pores in females; and two bold dark stripes from the snout to the base of the tail separated by a contrasting light vertebral stripe. It is the eighth species in the genus Dixonius. Lastly, we discuss the type locality of Phyllodactylus paviei, currently regarded as a junior subjective synonym of Dixonius siamensis.